A novel two-step sintering for nano-hydroxyapatite scaffolds for bone tissue engineering - Feng, Pei (Nature Publishing Group, 2014)
In this study, nano-hydroxyapatite scaffolds with high mechanical strength and an interconnected porous structure were prepared using NTSS for the first time. The first step was performed using a laser characterized by the rapid heating to skip the surface diffusion and to obtain the driving force for grain boundary diffusion. Additionally, the interconnected porous structure was achieved by SLS. The second step consisted of isothermal heating in a furnace at a lower temperature (T(2)) than that of the laser beam to further increase the density and to suppress grain growth by exploiting the difference in kinetics between grain-boundary diffusion and grain-boundary migration. The results indicated that the mechanical properties first increased and then decreased as T(2) was increased from 1050 to 1250°C. The optimal fracture toughness, compressive strength and stiffness were 1.69 MPam(1/2), 18.68 MPa and 245.79 MPa, respectively. At the optimal point, the T(2) was 1100°C, the grain size was 60 nm and the relative density was 97.6%. The decrease in mechanical properties was due to the growth of grains and the decomposition of HAP. The cytocompatibility test results indicated that cells adhered and spread well on the scaffolds. A bone-like apatite layer formed, indicating good bioactivity.